APLIKASI INVENTORY LABORATORIUM KOMPUTER BERBASIS WEB DI MTs EL-BAYAN MAJENANG - Riswanto, Beny (Jurnal Teknologi dan Bisnis, 2020)
The influence of information technology today has become an attraction for someone to fulfill many aspects of life including the economy, education, government and others. The development of information technology makes human work easier, faster and more accurate so that they do not waste so much energy and time. This Facility and Infrastructure Management application is designed to provide security in data storage in the field of infrastructure at MTs El-Bayan Majenang and also in computerized management of data in the field of facilities. On the basis of this theory explains the theories used in designing the system and also other supporting devices for the process of making this management application. The method used to design this application system uses the waterfall method. This management application is designed using the PHP programming language, using the Codeigniter framework MySQL database as data storage media. For the server here using apache and for design tools in the form of Use case diagram, Activity diagram and Entity Relationship Diagram (ERD)It can be concluded that with this management application, employees can be even better at storing data and also managing data on facilities and infrastructure because now the existing system is computerized